The spatial aspect of human rights: a framework for the structural and spatial analysis of human rights practice. Issue 4 (21st April 2021) - García Elena, Fátima
ABSTRACT: Space is a contingent matter in the application, monitoring, and overall experience of human rights. Political ecology, sociology, and, most recently, geography have addressed the dialectical space-human rights through environmental or urban justice struggles. In this paper, I introduce a framework that articulates the analysis of space and human rights. The framework features three functional facets of spatial structures and discusses how they intervene with the experience of rights. The purpose of this article is to introduce a novel theoretical framework that makes space a level for human rights research. This discussion fills a gap in the current human rights literature, supports the further integration of environmental variables and non-human entities in the human rights system, and defends the validity of non-traditional approaches for the development of the human rights project.